Neuromuscular Complications With SARS-COV-2 Infection: A Review - Katyal, Nakul; Narula, Naureen; Acharya, Sudeep; Govindarajan, Raghav (Frontiers in Neurology, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) cases were first reported in Wuhan, Hubei province of China in December, 2019. SARS- COV-2 primarily affects the cardio-respiratory system. Over the last few months, several studies have described various neurological sequelae of SARS-COV-2 infection. Neurological complications are more frequent in patients with severe respiratory infections. In this review, we have analyzed the current literature on neuromuscular complications associated with SARS-COV-2 and highlighted possible mechanisms of neuromuscular invasion. We reviewed 11 studies describing 11 cases of Guillain Barre syndrome (GBS), and 1 case each of Miller Fisher syndrome, Polyneuritis cranialis, Acute myelitis, Oculomotor paralysis and Bell's Palsy associated with SARS-COV-2 infection. Mean age of patients with GBS was 61.54 years, with standard deviation (SD) 14.18 years. Majority patients had fever and cough as the first symptom of SARS COV-2 infection. Mean time for onset of neurological symptoms from initial symptoms in 11 patients was 8.18 days, with SD of 2.86 days. Mean time to performing electro-diagnostic study from onset of neurological symptom was 6 days with standard deviation of 3.25. 6 patients had demyelinating pattern, 3 had acute sensory motor axonal neuropathy and 1 had acute motor axonal neuropathy on electro-diagnostic studies.